Risk-assessment V1.0: A new interactive software to develop risk assessment using MATLAB® (2018)
This article presents the use of an interactive computer tool developed in MATLAB® called RISKASSESSMENT v1.0, to perform market risk analysis of commercial products, through the development of cash flow, sensitivity analysis, and SpiderPlot graphics, which allow the identification of the economic-financial equilibrium point of a company. The tool facilitates the reduction of the uncertainty produced in the return on investment due to changes in the economic environment of the sector in which the company operates, through statistical techniques and tools that involve parameters such as the annual effective rate in the Colombian national currency, net present value, internal rate of return, period of recovery of capital, through a sensitivity analysis. To validate the effectiveness of using software in the development of risk analysis, a case study was conducted for an alcohol beverage sales business, where, based on the portfolio containing the product quantity, unit variable cost, sales price, percentage of sales growth and annual sales volume, in addition to detailed information on the initial investment, the cash flow with a 5-year horizon, the net present value, the internal rate of return, the period of capital recovery and the average accounting profitability are calculated. The tool also performs sensitivity analysis and SpiderPlot for each of the products. Finally, the program presented allows to calculate the annual cash flows in a fast and didactic way, which normally requires time and specialized training in a traditional exercise.